2016
DOI: 10.1111/oik.03462
|View full text |Cite
|
Sign up to set email alerts
|

Initiation ofBatrachochytrium dendrobatidisinfection in the absence of physical contact with infected hosts – a field study in a high altitude lake

Abstract: Understanding transmission is a critical prerequisite for predicting disease dynamics and impacts on host populations. It is well established that Batrachochytrium dendrobatidis (Bd), the amphibian fungal pathogen responsible for chytridiomycosis, can be transmitted directly, through physical contact with an infected host. However, indirect pathways of transmission remain poorly investigated. We conducted a five-week long field infection experiment at a high altitude mountain lake in the French Pyrenees to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…Previous studies have demonstrated that Bd occurs in the environment; given that amphibians can become infected in areas that do not contain infected amphibians (i.e., Courtois et al. , Fernández‐Beaskoetxea et al. , Voyles et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that Bd occurs in the environment; given that amphibians can become infected in areas that do not contain infected amphibians (i.e., Courtois et al. , Fernández‐Beaskoetxea et al. , Voyles et al.…”
Section: Discussionmentioning
confidence: 99%
“…Negative host-density-dependent Bd transmission risk cannot be explained without assuming that Bd exists in environment reservoirs for long periods of time, given that Bd transmission risk is nearly 100% at sites where host abundance is one individual. Previous studies have demonstrated that Bd occurs in the environment; given that amphibians can become infected in areas that do not contain infected amphibians (i.e., Courtois et al 2016, Fern andez-Beaskoetxea et al 2016, Voyles et al 2018). However, without knowing if Bd can reproduce or how long it persists in the environment, we cannot support the implied assumptions of a Bd environmental reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…; Courtois et al . ), but the nature of this transmission has rarely been quantified. We experimentally quantified the transmission function in the R. muscosa ‐Bd system and used these results, in combination with a dynamic model, to predict how the environmental zoospore reservoir affected the ability of Bd to invade an amphibian population.…”
Section: Discussionmentioning
confidence: 99%
“…Uninfected frogs can acquire Bd infection through contact with other infected frogs and through contact with zoospores in an environmental Bd pool (Courtois et al . ). To account for these different pathways, we fit two sets of transmission models to the data.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation